Impact of Days to Receivable on the Profitability of Exporting Coal Companies in Indonesia - Ferranti, Putri Andari; Hindardjo, Anton (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study examines the effects of exchange rates, export intensity, and days to receivable on the profitability of Indonesian coal exporting companies, using panel data from 2015 to 2023. The objective is to find if export intensity and exchange rate impedes the effect of days to receivable on profitability. Interaction analyses reveal that the positive impact of receivables on profitability diminishes with increasing exchange rates. Conversely, the interaction between days to receivable and export intensity does not significantly affect profitability. Therefore, it might be beneficial for Indonesian coal companies should explore implementing more flexible trade credit policies to enhance customer relationships, particularly during periods of rupiah appreciation.